2021
DOI: 10.3389/fpsyg.2021.628809
|View full text |Cite
|
Sign up to set email alerts
|

School Violence and Teacher Professional Engagement: A Cross-National Study

Abstract: School violence research has mainly focused on the impact on students. Very few studies, even fewer from a cross-cultural perspective, have examined the relationships between school violence and teacher professional engagement, and the role played by teacher self-efficacy and school climate related factors. The present study utilizes a SEM research methodology to analyze the 2013 TALIS data. The purpose is to understand and compare the relationships in four different cultural contexts; the U.S., England, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
(71 reference statements)
0
13
0
3
Order By: Relevance
“…Quando é oferecida a possibilidade de gerenciamento participativo da escola, com a parceria entre professores, alunos, familiares e comunidade, associada a adequação do relacionamento professor-aluno, o impacto negativo da violência escolar pode ser aliviado de forma significativa. A tomada de decisões em conjunto por esses setores, aliada a implementação de atividades lúdicas, recreativas, extracurriculares traz contribuições positivas ao ambiente escolar 2,10 . Também, o apoio de um mediador da comunidade identificado como "disciplina" chamou a atenção.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Quando é oferecida a possibilidade de gerenciamento participativo da escola, com a parceria entre professores, alunos, familiares e comunidade, associada a adequação do relacionamento professor-aluno, o impacto negativo da violência escolar pode ser aliviado de forma significativa. A tomada de decisões em conjunto por esses setores, aliada a implementação de atividades lúdicas, recreativas, extracurriculares traz contribuições positivas ao ambiente escolar 2,10 . Também, o apoio de um mediador da comunidade identificado como "disciplina" chamou a atenção.…”
Section: Discussionunclassified
“…Contudo, os professores também estão propensos a serem vítimas de violência dos seus alunos, de forma insidiosa ou crônica no local de trabalho ou por meio digital. Sua tipologia inclui agressões verbais, físicas, assédios sexuais, psicológicas (descaso, desrespeito, discriminação quanto à identidade de gênero ou orientação sexual) e patrimoniais [6][7][8][9][10][11][12][13] .…”
Section: Introductionunclassified
“…In South Korea, at least once did teachers inflict their acts of emotional maltreatment on students—with the number of approximately 20%—in the form of mockery or humiliation ( Cheung et al., 2019 ). Meanwhile, 80% of American teachers encountered at least one of the 11 different acts of violence on campuses during their previous school years ( Yang et al., 2021 ). More seriously, the prevalence of physical fighting among 68 low-to-middle-income countries is more than 36% and serious injuries account for nearly 43% ( Han et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to current research across nations, school violence is linked to suicidal intentions, poor mental health, substance abuse, and truancy among students ( Senanayake et al., 2019 ; Pengpid and Peltzer, 2019 ; Beck et al., 2016 ; Denny et al., 2016 ). Regarding violence between students and teachers, an increasing number of research papers from both developed and developing nations have demonstrated that school violence is associated with teachers' disengagement, intention to leave the job, and other undesirable effects such as emotional well-being ( Yang et al., 2021 ). They also discovered a consistent trend throughout the United States, England, South Korea, and Mexico that teachers' perceptions of insecurity and vulnerability resulting from school violence have a detrimental influence on their self-efficacy, which could lead to lower involvement in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Insults, fight, research on physical and psychological characteristics, socio-economic status, and religious or ethnic affiliation are all examples of violent incidents at school ( Cascardi et al, 2018 ). School violence makes classrooms and school environments unhealthy, makes it hard for teachers to teach, and disrupts the relationship between students and teachers ( Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%